2021
DOI: 10.3389/fonc.2021.636068
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T Cell Therapy Management and Safety: A Practical Tool From a Multidisciplinary Team Perspective

Abstract: PurposeThe use process for chimeric antigen receptor T (CAR-T) cell drugs is complex and has been associated with a number of potentially severe complications, which requires management by a multidisciplinary team. Pharmacists are a key element in the team and have roles and responsibilities. Our objective was to develop a structured and practical guide that supports hospital pharmacist responsibilities and defines specific activities in a CAR-T cell therapy program, specifically in Europe.MethodsA literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
(47 reference statements)
0
10
0
1
Order By: Relevance
“…CAR-T therapy is an innovative and effective therapeutic option for the treatment of hematological malignancies refractory to previous treatment lines or multiple relapses [1][2][3][4][5][6][7][8][9][10]12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]32,34,[37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR-T therapy is an innovative and effective therapeutic option for the treatment of hematological malignancies refractory to previous treatment lines or multiple relapses [1][2][3][4][5][6][7][8][9][10]12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]32,34,[37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…As it is an immunological therapy, when the antigen receptors are introduced into the body, T lymphocytes trigger an immune response that attacks the tumor but can also attack healthy cells. The two most frequent adverse effects of the infusion of CAR-T cells are neurotoxicity syndrome associated with immune effector cells (ICANS) and cytokine release syndrome (CRS) [ 1 , 14 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The value of pharmacist-led team care in pharmacotherapies has been demonstrated in numerous studies ( Yamamoto et al, 2018 ; Escudero-Vilaplana et al, 2020 ; Satsuma et al, 2020 ; Ji et al, 2021 ; Jia et al, 2021 ; Marzal-Alfaro et al, 2021 ; Miura et al, 2021 ; Xu et al, 2021 ). The results of this study revealed that pharmacist-urologist collaborative management can also improve care for patients with CRPC receiving enzalutamide in an ambulatory care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cooperation should be secured with departments other than those of the specialists, such as the intensive care unit (ICU) and the neurology department, before the operation [19]. In addition, the involvement of administrative departments, such as legal affairs and finance, are also necessary for the hospital to establish new treatment modalities [21]. When patients receive CAR-T-cell therapy, numerous personnel are involved in the many treatment steps mentioned above [22,23].…”
Section: Establishment Of An Ecosystem For Actual Clinical Use Of Reg...mentioning
confidence: 99%